CO2 as moderator for biomass gasification - Pohorely, M.; Jeremias, M.; Svoboda, K.; Kamenikova, P.; Skoblia, S.; Beno, Z. (Elsevier, 2013)
Biomass can be converted into gaseous fuel by high-temperature reactions with a gasifying agent. The gasifying agent consists, in most cases, of oxygen and of a moderator, which is usually water vapour. Here we show that waste CO2 can be used instead of, or together with, water vapour to moderate the process of biomass gasification in a catalytic fluidized bed of dolomitic limestone. Such use of CO2 increased substantially the carbon and energy conversion efficiency and decreased the amount of tars in the produced gas.
Keywords: Dolomite; Limestone; Catalyst; Fluidized bed; Primary measures